Perbuatan Pidana Bughah dalam Hukum Pidana Islam - Riswadi Riswadi (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2014)
During this time, the issue bughah; separatists; the plots tend to receive less attention among Muslim intellectuals. Bughah deeds have made part of a crime (against the law). In Islamic law, a criminal act bughah also still have a different understanding. There is mention, that act bughah set with criminal types had, qishas or criminal ta'zir. Restrictions specified types of criminal is understood in terms of the act, the relationship with the rights, or any other cause in connection with the action against the state or government. Therefore, the range of possibilities can contain different perceptions and motives when trying to explain the quality of the act bughah. Similarly, environmental factors, socio-historical, cultural and political developments also color differences in terms of the substance of the type of criminal act bughah category. Kata kunci: pidana, bughah dan pidana Islam